2004
DOI: 10.1111/j.1439-0426.2004.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics and lipid fraction quality of sardines (Sardina pilchardus W.): influence of sex and length

Abstract: An experimental investigation was carried out on sardines\ud (Sardina pilchardus W.) with the aim to evaluate the influence of sex and total length (TL) on total weight (TW) and fillet\ud weight (FW), chemical composition, and lipid fraction quality.\ud Special emphasis was given with respect to the content of\ud polyunsaturated fatty acids (PUFA), which are considered\ud important from a dietary, nutritional, and functional point of view. Sardines were subdivided as a function of TL and sex. Four groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
(30 reference statements)
9
24
1
1
Order By: Relevance
“…This finding is in agreement with those of Caponio et al (2004), Ennouri et al (2013), and Ben Rebah et al, (2014) in their studies on Sardina pilchardus, Sarinella aurita, and Liza aurata, from the Ionian Sea, the Gulf of Tunis and the Gulf of Gabès, respectively. However, according to Wallace (1991) mackerel fat fillets content values are ranging between 25 and 30% in December and are around 5% in May, when fish spawns.…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with those of Caponio et al (2004), Ennouri et al (2013), and Ben Rebah et al, (2014) in their studies on Sardina pilchardus, Sarinella aurita, and Liza aurata, from the Ionian Sea, the Gulf of Tunis and the Gulf of Gabès, respectively. However, according to Wallace (1991) mackerel fat fillets content values are ranging between 25 and 30% in December and are around 5% in May, when fish spawns.…”
Section: Chemical Compositionsupporting
confidence: 92%
“…Moreover, water temperature is the most important factor influencing PUFA synthesis in fishes. Temperature variations influence desaturase and synthesize enzyme activities with a direct effect, or by long term adaptative process-leading to the synthesis of omega-3 fatty acids (De Torrengo and Brenner, 1976;Farkas and Csengeri, 1976;Caponio et al, 2004).…”
Section: Fatty Acids Compositionmentioning
confidence: 99%
“…oil:meal ratios), collected for industrial/biotechnological purposes, in reconstructing the historical variation in reproductive potential is indisputable (Schülein et al 1995, Paiting et al 1998, Marshall et al 1999. Moreover, although size may influence the chemical characteristics of sardines (Caponio et al 2004), other studies with small pelagic fish species have revealed no relationship between size (or age) and proximate composition (e.g. Van Pelt et al 1997, Foy & Paul 1999, Payne et al 1999, Eder & Lewis 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was possible to accurately estimate the energetic condition of adult European sardine based on several empirical bioenergetic models (Table 3) 1984 1985 1986 1987 1988 1989 1990 1991 1992 1993 1994 1995 Body energy density (kJ g , positive values mean offshore transport). Seasonally adjusted time series are represented by the thick grey line size, the validity of the models for juveniles may be reduced, because sardine juveniles may allocate energy differently than adults (Caponio et al 2004 (1) 0.73 (0.12) 6.10** < 0.0001 Table 4. Sardina pilchardus.…”
Section: Biochemical Indicators Of Sardine Conditionmentioning
confidence: 99%
“…Ikan mengeluarkan lebih banyak energi dengan lemak sebagai sumber utamanya (Wassef dan Shehata, 1991;Caponio et al, 2004). Jaringan kaya lemak biasanya diketahui mengandung trigliserida sebagai lemak utama, sedangkan jaringan rendah lemak dapat didominasi oleh fosfolipid pada ikan nila (Sargent et al, 1999).…”
Section: Hasil Dan Pembahasan Kadar Proksimat Lemakunclassified